Հայաստանի եզդիների «Բուկա բարանե» («Անձրեւի հարս») եւ մյուս անձրեւաբեր ծեսերը - Ռոման Հովսեփյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Обряд "бука баранэ" (переводится как "невестка дождя") практиковался среди езидов, курмандж и язычного населения Армении в прошлом и иногда также в наши дни. The ceremony of “buka barane” (translated as “bride of rain”) was practiced in the past and sometimes also in our days amongest kurmanji speaking population of the Republic of Armenia.
Keywords: Manners and customs